In silico analysis of the antigenic properties of iron-regulated proteins against Neisseria meningitidis - Rahman, Md.Shahedur; Biswas, Chayon; Biswas, Polash Kumar; Kader, Md. Ashraful; S. M., NurAlam; Sonne, Christian; Kim, Ki-Hyun (MDPI, 2020)
Neisseria meningitidis is a commensal pathogen that causes infectious cerebrospinal disease in people of all ages. The multivariate role of six disease-causing polysaccharide serotypes is found to play a crucial role in developing vaccines (or general treatment strategies) to treat this emerging pathogen. Iron is a crucial transition metal for N. meningitidis. Proteomic analysis data could be valuable for vaccine design. Here, we conduct a comparative study using computational bioinformatic tools to identify the most effective iron-regulated outer membrane proteins (OMPs) as immunogenic targets for a potential vaccine against N. meningitidis. The basic properties of N. meningitidis OMPs are explored for flexibility, solubility, hydrophilicity, beta-turns, and overall antigenic probability. Results of our study suggest that iron-regulated OMPs are flexible and soluble in water with high densities of conformational B-cell epitopes. As such, they can be recommended as a novel candidate for a vaccine against N. meningitidis both in vitro and in vivo.